Bezpośrednia sprzedaż produktów rolniczych w warunkach członkostwa Polski w Unii Europejskiej - Dziedzic, Sylwia (Direct Sale of Agricultural Products in the Conditions of Polish Membership in the European Union, 2005)
Direct sale of meat can create special problems for an agricultural manufacturer.Initiating all changes legal provisions will contribute to the settlement of principles and methods of direct sale of agricultural products. Despite that they will force the Polish farmer accept the considerably higher standards then the hygienic. They will secure the behaviour of indispensable requirements, particularly important in case of direct sale of meat products.The direct sale gives the chance the procurement from farmers additional earnings.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 186-191